Skeletal Class III correction in permanent dentition using reverse twin block appliance and fixed mechanotherapy - Harpreet Singh; Pranav Kapoor; Poonam Sharma; Raj Kumar Maurya; Tanmay Mittal (Elsevier, 2018)
The orthodontic management of patients with Class III malocclusion poses numerous prognostic and treatment challenges to the clinician. Various removable, orthopaedic, myofunctional and fixed appliances have been recommended for the correction of Class III malocclusion. The Reverse Twin Block (RTB) is a simple and well tolerated appliance which has often been used for the early management of such cases in mixed dentition. Cases reporting use of RTB in permanent dentition are however, limited. This article presents an insight into the encouraging results of reverse twin block (RTB) appliance used in conjunction with fixed mechanotherapy for the successful treatment of a 12-year-old patient presenting with skeletal Class III malocclusion and a concave facial profile. The RTB appliance helped establish a favourable environment for unrestricted maxillary growth, at the same time redirecting the mandibular growth to a clockwise direction and correcting the incisal relationship. The favourable treatment outcome and long-term stability achieved substantiates the feasibility of RTB appliance in mild to moderate skeletal Class III malocclusions in permanent dentition cases. Keywords: Skeletal Class III, Reverse twin block, Fixed appliance, Permanent dentition